Why People Dual Screen Political Debates and Why It Matters for Democratic Engagement. Issue 2 (3rd April 2017) - Chadwick, Andrew; O'Loughlin, Ben; Vaccari, Cristian
Abstract : Dual screening during televised election debates is a new domain in which political elites and journalists seek to influence audience attitudes and behavior. But to what extent do non-elite dual screeners seek to influence others, particularly their social media followers, social media users in general, and even politicians and journalists? And how does this behavior affect short- and longer-term engagement with election campaigns? Using unique, event-based, panel survey data from the main 2015 UK general election debate (Wave 1 = 2, 351; Wave 2 = 1, 168) we reveal the conditions under which people experience agency, empowerment, and engagement now that social media have reconfigured broadcast political television.